Exploring the Impact of Effective Learning Communication on the Motivation of Elementary School Students in Poso City - Sartika Andi Patau (STAI Hubbulwathan Duri, 2024)
This study explores the influence of effective learning communication on the motivation of elementary students in Poso City, Central Sulawesi. Adopting a quantitative approach, the research was carried out across multiple elementary schools, with the schools forming the study's population. The sampling was purposive, targeting students from third to sixth grade who could understand and respond to the questionnaire, with the ability to communicate, absorb, and feedback information, as well as interact effectively with educators and peers. Data collection entailed administering questionnaires and examining written documents, while simple linear regression analysis was used to evaluate the impact of effective communication (independent variable) on learning motivation (dependent variable). The findings reveal that effective communication significantly boosts student motivation in elementary schools, underscoring its necessity for impactful teaching. The study posits that while effective communication is crucial at the elementary level, its importance escalates in higher education due to the diversity in student characteristics and the intensified teacher-student communication. Hence, it suggests the need for adaptable communication strategies to ensure effective teaching and learning across different educational levels.